2011
DOI: 10.1152/ajpheart.01080.2010
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-210 is upregulated in hypoxic cardiomyocytes through Akt- and p53-dependent pathways and exerts cytoprotective effects

Abstract: microRNA-210 (miR-210) is upregulated in hypoxia, but its function in cardiomyocytes and its regulation in response to hypoxia are not well characterized. The purpose of this study was to identify upstream regulators of miR-210, as well as to characterize miR-210's function in cardiomyocytes. We first showed miR-210 is upregulated through both hypoxia-inducible factor (HIF)-dependent and -independent pathways, since aryl hydrocarbon nuclear translocator (ARNT) knockout mouse embryonic fibroblasts (MEF), lackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
140
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 42 publications
11
140
1
Order By: Relevance
“…6 These miRNAs have also been shown to play a role in controlling cell growth, apoptosis, senescence and autophagy in a p53-dependent fashion ( Table 1). [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Recently, we identified miR-1246 as another novel p53 target miRNA. Interestingly, this miRNA regulates the expression of DYRK1A, a Down syndrome-associated kinase, 21 which inactivates a nuclear transcriptional factor called NFAT1C by phosphorylating it and preventing it from nuclear import.…”
Section: Mir-1246mentioning
confidence: 99%
“…6 These miRNAs have also been shown to play a role in controlling cell growth, apoptosis, senescence and autophagy in a p53-dependent fashion ( Table 1). [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Recently, we identified miR-1246 as another novel p53 target miRNA. Interestingly, this miRNA regulates the expression of DYRK1A, a Down syndrome-associated kinase, 21 which inactivates a nuclear transcriptional factor called NFAT1C by phosphorylating it and preventing it from nuclear import.…”
Section: Mir-1246mentioning
confidence: 99%
“…A direct target of miR210 in human HCC cells is apoptosis-inducing factor M3 (AIFM3), also referred to as AIF-like, as it is a gene homolog of AIF. AIFM3 is mainly present in mitochondria, resulting in cytochrome c release and apoptosis in a caspase-dependent manner (96,97). AIFM3 downregulation by small interfering RNA-impaired radiation-induced apoptosis in human HCC cells was associated with reduced miR210 expression.…”
Section: Mirnas For Prediction Of Prognosis In Hccmentioning
confidence: 94%
“…Overexpression and loss-of function studies have revealed roles for individual miRNAs in heart disease (31,39,40). For example, miR-208 is expressed from the intron of myosin heavy chain 6 and is expressed specifically in cardiac and slow skeletal muscle (41).…”
Section: Mirnas Regulate Cardiac Functionmentioning
confidence: 99%